‘Striving to achieve control’. Registered nurses’ experiences of palliative care quality during the COVID-19 pandemic – a qualitative study - Tuva Sandsdalen; Ann Karin Helgesen; Vigdis Abrahamsen Grøndahl; Carina Bååth; Maria Larsson; Christina Melin Johansson; Cecilia Olsson; Maria Tillfors; Jane Österlind; Reidun Hov; Marie Dahlen Granrud (BMC Palliative Care)
Abstract Background Providing quality palliative care during a pandemic was challenging. Both specialist and community healthcare services cared for patients that faced life-threatening illness and who were influenced by the restrictions of the COVID-19 pandemic. Little knowledge has yet been provided on how registered nurses (RNs) experienced the palliative care quality during the COVID-19 pandemic. The aim of this study was to explore RN’s experiences of providing palliative care quality during the COVID-19 pandemic. Methods This qualitative study had a descriptive design. Semi-structured individual interviews were conducted between November 2021 and January 2022 with 18 RNs who worked in intensive care units in hospitals, dementia care or palliative care units in nursing homes in Norway during the pandemic. Data were analysed by using qualitative content analysis. The study was conducted and reported according to the COREQ’s checklist. Results Analysis of the data resulted in an overall theme: ‘Striving to achieve control’. This theme comprised six categories: (1) when the toolbox does not fit; (2) protective equipment—social distance and opportunities for closeness; (3) unpredictable workday; (4) the right person to the right assignment at the right time; (5) presence and absence of relatives and friends; and (6) situations that required creativity. RNs had various experiences regarding how the quality of care was perceived; being worse, preserved, or in some cases even better than before the pandemic. Conclusions The provision of quality palliative care was experienced by RNs as challenging during the pandemic. The pandemic forced them to be creative and to strive for control to provide the best palliative care possible given the situation. The results of this study may contribute to important knowledge for leaders, policy makers and RNs to learn from the COVID-19 pandemic and planning for future pandemics or crises. Especially to optimise factors perceived by RNs to be important for the palliative care quality, related to the specific situation and care context, to include the perspectives of those involved and take into consideration the time perspective of the pandemic.